Anti-Mycoplasma Activity of Daptomycin and Its Use for Mycoplasma Elimination in Cell Cultures of Rickettsiae - Wiwit Tantibhedhyangkul; Ekkarat Wongsawat; Sutthicha Matamnan; Naharuthai Inthasin; Jintapa Sueasuay; Yupin Suputtamongkol (MDPI AG, 2019)
Mycoplasma contamination detrimentally affects cellular functions and the growth of intracellular pathogens in cell cultures. Although several mycoplasmacidal agents are commercially available for sterile cell cultures, they are not applicable to rickettsia-infected cells. In our attempt to find an anti-mycoplasma drug for contaminated rickettsial cultures, we determined the susceptibilities of three common Mycoplasma species to daptomycin. Mycoplasma orale and M. arginini showed low-level resistance to daptomycin (minimum inhibitory concentration, MIC = 2 mg/L), whereas M. hyorhinis was high-level resistant (MIC = 32 mg/L). However, some Mycoplasma isolates developed higher resistance to daptomycin after failed treatments with inadequate doses or durations. An aminoglycoside (gentamicin) was still active against M. hyorhinis and could be used in Orientia cultures. For complete eradication of mycoplasmas in Rickettsia cultures, we recommend a 3-week treatment with daptomycin at 256 mg/L. In contaminated Orientia cultures, daptomycin at 32 mg/L was effective in eradicating M. orale, whereas either gentamicin or amikacin (100 mg/L) was effective in eradicating M. hyorhinis. Unlike each drug alone, the combinations of daptomycin plus clindamycin and/or quinupristin/dalfopristin proved effective in eradicating M. hyorhinis. In summary, our study demonstrated the in vitro anti-mycoplasma activity of daptomycin and its application as a new mycoplasma decontamination method for Rickettsia and Orientia cultures.